Microautophagy in the visceral endoderm is essential for mouse early development - Wada, Yoh (Landes Bioscience, 2013)
During early embryogenesis, before the conceptus forms the placenta, maternal nutrients as well as signaling molecules must reach the embryo proper through a tightly sealed epithelial tissue, the visceral endoderm (VE). The VE serves as a signaling center for embryogenesis, where exocytic and endocytic processes integrate signal production, perception and termination. However, the endocytic process in this important tissue has not been well characterized. We show that endocytic delivery to the lysosomes occurs via RAB7-dependent microautophagy. This process is essential for early mammalian development.